2022
DOI: 10.1108/jieb-02-2022-0012
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of short-term study abroad outcomes and an agenda for future research

Abstract: Purpose The purpose of this paper is to serve as a comprehensive review of short-term study abroad (STSA) outcomes to help guide future STSA and study abroad (SA) scholars and practitioners in the further development of the field. Design/methodology/approach This paper is the first comprehensive and systematic review of all outcomes of STSA programs within the SA body of research based on 156 papers. Findings The study provides the first comprehensive classification of all previously studied STSA outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 128 publications
0
3
0
Order By: Relevance
“…STSA programs are often seen as a way for educators and policymakers to foster global or regional integration, in addition to achieving academic goals (Pedersen, 2010; Tran et al ., 2021). However, research on STSA programs and students tends to focus on the knowledge and skills gained, such as language and cultural proficiency, while subjective evaluations of the sojourn experience, which may further shape STSA students' future migrations, are not fully explored (Bradly and Iskhakova, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…STSA programs are often seen as a way for educators and policymakers to foster global or regional integration, in addition to achieving academic goals (Pedersen, 2010; Tran et al ., 2021). However, research on STSA programs and students tends to focus on the knowledge and skills gained, such as language and cultural proficiency, while subjective evaluations of the sojourn experience, which may further shape STSA students' future migrations, are not fully explored (Bradly and Iskhakova, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…For STSA students, achieving their goals during their sojourn is likely to be an important factor in their feeling of worthwhileness. Studies have indicated that STSA students may have diverse objectives for their time abroad, including academic pursuits, leisure activities and a desire to develop a deeper understanding of the host culture and society (Doerr, 2012;Bradly and Iskhakova, 2023). Therefore, having a desire to engage with the host culture and people can significantly impact the overall experience for STSA students.…”
Section: Attitude Towards the Host Culture And Societymentioning
confidence: 99%
See 1 more Smart Citation